2016
DOI: 10.1002/ets2.12099
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pre‐K Age 4 Learning Standards and Their Role in Early Childhood Education: Research and Policy Implications

Abstract: Currently in the United States, 50 states, 5 territories, and the District of Columbia have established prekindergarten (pre‐K) age 4 learning standards that are intended to outline skills and knowledge that set children on a path to success in kindergarten and upcoming grades. These standards are emphasized as a centralizing force in early childhood education, providing a bridge strengthening ties between preschool and elementary grades. This report presents a national study of pre‐K age 4 learning standards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Similar to prior research (DeBruin-Parecki & Slutzky, 2016), this review found that every state (and a few territories) had developed ELDS, though many state documents were organized differently. For example, some ELDS were contained in a single document whereas others separated their ELDS into separate documents by general or specific domains, or age bans.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Similar to prior research (DeBruin-Parecki & Slutzky, 2016), this review found that every state (and a few territories) had developed ELDS, though many state documents were organized differently. For example, some ELDS were contained in a single document whereas others separated their ELDS into separate documents by general or specific domains, or age bans.…”
Section: Discussionsupporting
confidence: 65%
“…This review suggests most state ELDS documents supported the learning needs of all young children, which is an improvement over previous reviews of state ELDS (DeBruin-Parecki & Slutzky, 2016; Scott-Little et al, 2006, 2009). While this finding was an encouraging step toward the realization of a unified curriculum framework for all young children, this review also documented that most state ELDS lacked explicit guidance and direction about the administration and use of ELDS in young children with developmental delays.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…should know and should be able to do before entering kindergarten (DeBruin-Parecki & Slutzky, 2016). ECE curricula, on the other hand, set goals for the knowledge and skills that children should acquire in an educational setting, and support educators' plans for providing the day-to-day learning experiences to cultivate those skills, such as daily lesson plans, materials, and other pedagogical tools (Duncan et al, 2015).…”
Section: Curriculum Early Learning Standards Are Defined As Expectatmentioning
confidence: 99%